Improving Opportunities in Supply Chain Processes Using the Internet of Things and Blockchain Technology - Samar Raza Talpur; Alhamzah F. Abbas; Nohman Khan; Sobia Irum; Javed Ali (International Journal of Interactive Mobile Technologies (iJIM), 2023)
The present study looks at how the internet of things and blockchain technology might be used to improve prospects in supply chain procedures. The current pandemic has highlighted the significance of resilient and dependable supply chain systems that are less dependent on humans and more efficient in cycling goods supply chains. The present study included and excluded records from two recognised databases, Scopus and Web of Science, using the PRISMA declaration 2020. After following the inclusion and exclusion criteria details, investigated the forty-seven articles with two significant data streams (traceability of supply chain management, resin and sustainability). Results illustrated that in today’s environment, the rivalry has shifted from "firm vs firm" to "supply chain vs supply chain." As a result, the ability to optimise the supply chain has arisen as a significant issue for organisations seeking a competitive advantage. However, it has become increasingly challenging to traceability of products and merchandise while they are moving through the value chain network. The Internet of Things (IoT) applications and blockchain technologies can help companies observe, track, and monitor products, activities, privacy, security and processes within their respective value chain networks. Other applications of IoT include product monitoring to optimise operations in warehousing, manufacturing, food supply chain and transportation. Combined with IoT, Blockchain technology can enable various application scenarios to enhance supply-chain transparency and trust. When combined, IoT and Blockchain technology can increase the effectiveness and efficiency of modern supply chains. First, we illustrate how deploying Blockchain technology in combination with IoT infrastructure can streamline and benefit modern supply chains and enhance value chain networks. Second, we also identified that the resilience of big data analytics, machine learning and artificial intelligence is helpful for the sustainable development of social, economic and environmental contexts.